QUALITATIVE CHARACTERIZATION OF PHYTOCHEMICALS PRESENT IN THE BARK FROM SOME SELECTED TREE SPECIES (International Association of Biologicals and Computational Digest, 2022)
Plants have tremendous properties which are used in our day to day life. Majorly plant used as source of food, fabrics and medicine. Hence the identification of plants is very essential process. Generally, plants are identified by their primary structures of growth; such as leaves, flowers and fruits. In the absence of these organs bark is the only outermost region of the plants; through which identification of the particular plant can be identified. Bark is the secondary structure and which persist throughout the plant life. Bark is composed of various tissues which are incorporated with many phyto-chemicals which are photosynthetic products as well as bio products jointly known as photosynthates. Due to the presence of these photosynthates bark are used as medicine. Hence the preparation of data that includes information about phytochemical present in bark leads us to the new aspect towards bark for identification as well as pharmacological purpose.
Keywords: Pharmacognosy, Bark, Identification, Phyto-chemicals, Photosynthates.